Pengaruh Peran Gender, Masculine Dan Feminine Gender Role Stress Pada Tenaga Administrasi Universitas Brawijaya - Tulus Sabrina; Retty Ratnawati; Endah Setyowati (Indonesian Journal of Women's Studies, 2016)
Abstract This study aims to explain and analyze the influence of gender roles, Masculine and Feminine Gender Role Stress against work commitment. This research uses quantitative approach, with purposive sampling technique. The respondents were UB's administrative staff of 96 respondents. The data were collected by using questionnaires. The analysis of this study used the simultaneous significance test (F test) and Partial significance test (t test). The results of gender role deception show that male and female respondents tend to have a feminine gender role. The result of F test shows that there is influence of gender role, Masculine Gender Role Stress (MGRS), Feminine Gender Role Stress (FGRS) together with significant work commitment on male respondent, (F count> F table) F arithmetic 4,435 < F table 2,811, and big influence 22,8%. While Sig.F 0,008 <0,05. However, the results of the female respondents in the F test did not show significant results, because (F arithmetic <F table) F arithmetic 1.438 <F table 2.822, with a large influence of 9.1%. From the result of t-test, the significant result is only evidenced from the influence of gender role on work commitment (sign 0,326) on male respondent. While the result of MGRS sera FGRS test on work commitment both on male and female respondents did not show significant result. Nevertheless, the measurements of MGRS and FGRS indicate an indication of stress on male and female respondents. In other words, masculine and feminine stereotypes are one source of stress and problems in both male and female respondents.